Comparing the effect of elevated pCO2 and temperature on the fertilization and early development of two species of oysters - Parker, L M; Ross, P M; O'Connor, W A (Marine Biology, 2010)
This study compared the synergistic effects of elevated pCO2 and temperature on the early life history stages of two ecologically and economically important oysters: the Sydney rock oyster, Saccostrea glomerata and the Pacific oyster, Crassostrea gigas. Gametes, embryos, larvae and spat were exposed to four pCO2 (375, 600, 750, 1,000 μatm) and four temperature (18, 22, 26, 30°C) levels. At elevated pCO2 and suboptimal temperatures, there was a reduction in the fertilization success of gametes, a reduction in the development of embryos and size of larvae and spat and an increase in abnormal morphology of larvae. These effects varied between species and fertilization treatments with S. glomerata having greater sensitivity than C. gigas. In the absence of adaptation, C. gigas may become the more dominant species along the south-eastern coast of Australia, recruiting into estuaries currently dominated by the native S. glomerata. © 2010 Springer-Verlag.